From Commercial Enzymes to Biocatalysts Designed by Protein Engineering - Bornscheuer, Uwe T. (Synlett, 2013)
This account provides a personal view on the development of biocatalysis over the last two decades. Examples include the use of commercial enzymes, such as lipases, (recombinant) esterases, transaminases, and Baeyer–Villiger monooxygenases for the synthesis of optically pure compounds. The opportunity provided by modern protein engineering methods to tailor design an enzyme for a given scientific problem (substrate scope, selectivity, stability) is emphasized together with concepts to boost this technology in terms of timelines and success.1 Introduction 2 Unexpected Discoveries2.1 To Protect and Serve2.2 ‘Abnormal’ Access to β-Amino Acids3 Defined Enzyme Is Better Than Crude Extract4 New Horizons Opened by Protein Engineering4.1 Random Mutagenesis Can Give Random Results5 Exploring Sequence and Structure Databases5.1 Massive Alignment Identifies Evolutionary Variations5.2 Fixing Wrong Annotations Can Yield a Toolbox of Novel Enzymes6 Conclusion
Keywords: asymmetric catalysis; biocatalysis; enantioselectivity; enzymes; kinetic resolution; protein engineering